204k views
16 votes
HELP HELP I don’t know how to do thissssss

HELP HELP I don’t know how to do thissssss-example-1
User Salaam
by
4.7k points

2 Answers

1 vote

Explanation:

p(x) + q(x) = x^3 - 3x - 1 + x - 1= x^3 - 2x - 2

p(x) - q(x) = x^3 - 3x - 1 - x + 1 = x^3 - 4x

p(x) x q(x) = (x^3 - 3x - 1) (x-1) = x^4- x^3 - 3x^2 +3x -x +1 = x^4 - x^3 -3x^2 + 2x +1

p(x) : q(x) = x^3 - 3x - 1/ x - 1= x( x^2 - 3 - 1) / x - 1

User Treffer
by
5.2k points
8 votes

Answer:

see below

Explanation:


p(x)=x^3-3x-1 and
q(x)=x-1


p(x)+q(x)=(x^3-3x-1)+(x-1)=x^3 -2x-2


p(x)-q(x)=(x^3-3x-1)-(x-1)=x^3 -3x-1-x+1=x^3-4x


p(x) * q(x)=(x^3-3x-1)(x-1)=x^4-x^3-3x^2+2x+1


(p(x))/(q(x)) =(x^2-3x-1)/(x-1) =x^2+x-2-(3)/(x-1)

User Espinal
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.